The Multi-Tenant Extension of Traditional Business Process Management Systems to Support BPaaS - Yu, Dongjin; Wang, Jiaojiao; Su, Jianwen; Huang, Binbin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2016)
BPaaS, or Business Process as a Service, is an advanced model of SaaS in which the Business Process Management System is deployed as a shared, centrally-hosted service without the need for users to deploy and maintain additional on-premise IT infrastructure. BPaaS leverages economies of scale and isolates the process management from domain business, by serving a large number of tenants. In this paper, we present an architectural design of a BPaaS system and its two implementations, called jBPM4S and ActivitiEx respectively. These extensions of two well-known open-source Business Process Management Systems, i.e., jBPM and Activiti, provide generic and unified process management services that are unrelated to specific business operations invoked on demand by tenants. To accomplish this, the extensions cleanly separate the business data from process execution to isolate tenants. An extensive case study is presented to demonstrate the usability and efficiency of the extensions, and difference with the traditional BPMS approach.